Usaha Konservasi Eksitu terhadap Bibit-bibit yang Dikoleksi dari Eksplorasi Botani di Taman Nasional Gunung Gede Pangrango - Imawan Wahyu Hidayat; Fitri Kurniawati; Yudi Suhendri (Postgraduate, University of Mataram, 2023)
A botanical exploration and collection were already conducted in March 2019 in Pasir Banteng and Pasir Pogor, Mount Gede Pangrango National Park, Indonesia, by a staff team from Cibodas Botanic Gardens (CBG). The following steps are to ensure these plants will be vigorous and survive in the nursery, which will later be ready to be planted and displayed as a garden collection. This study aimed to describe a series of treatments and management of these collections, analyze the survivorship level in the nursery, and record which seedlings were successfully planted in the garden. We explained the plant mainteÂnance used a qualitatively-descriptively method; the survivorship level was measured based on the proportional numbers of the survived individuals; the planted seedlings in the garden were recorded from the field observation. The findings showed that in the first three months of maintenance, seedlings occurred a large amount of mortality. Next, from June 2019 to August 2020, the seedlings performed good development with no mortaliÂty reported. In September 2020, as many as 13 specimens experienced mortality. At the end of December 2020, the total crude mortality was 41 specimens, and the survivorship level was 75.15%. All the orchid specimens have been planted as the garden collecÂtions